SARS-CoV-2 Infection and Testing Experiences in a Nationwide Sample of Transgender and Gender-Diverse Adults, June–December 2021. (March 2023) - Wirtz, Andrea L.; Adams, Dee; Poteat, Tonia C.; Beckham, S. Wilson; Miller, Marissa; Brown, Carter; Reisner, Sari L.
Objectives: COVID-19 surveillance data are rarely collected or disaggregated by gender identity in the United States. We quantified COVID-19 testing experiences and SARS-CoV-2 infection history among transgender and gender-diverse (TGD) people to inform testing strategies and public health responses. Methods: From June 14 through December 16, 2021, TGD adults enrolled in a US nationwide online survey with optional SARS-CoV-2 antibody testing. We used multinomial regression analyses to identify correlates of suspected and confirmed SARS-CoV-2 infection (vs no known infection). We identified correlates of inability to access COVID-19 testing when needed using generalized linear models for binomial variables. Results: Participants (N = 2092) reported trans masculine (30.5%), trans feminine (27.3%), and nonbinary (42.2%) gender identities. Ten percent of respondents had a confirmed history of SARS-CoV-2 infection, and 29.8% had a history of suspected SARS-CoV-2 infection. Nonbinary gender (adjusted prevalence ratio [aPR] = 1.68; 95% CI, 1.12-2.53), experiencing homelessness (aPR = 1.65; 95% CI, 1.05-2.60), and food insecurity (aPR = 1.45; 95% CI, 1.03-2.04) were associated with confirmed SARS-CoV-2 infection. Food insecurity (aPR = 1.38; 95% CI, 1.10-1.72), chronic physical health condition (aPR = 1.44; 95% CI, 1.15-1.80), chronic mental health condition (aPR = 3.65; 95% CI, 2.40-5.56), and increased anticipated discrimination scores (aPR = 1.03; 95% CI, 1.01-1.05) were associated with suspected SARS-CoV-2 infection. Thirty-four percent (n = 694 of 2024) of participants reported an inability to access COVID-19 testing when needed, which was associated with Latinx or Hispanic ethnicity, inconsistent telephone access, homelessness, disability, and transportation limitations. The majority (79.4%) reported a complete COVID-19 vaccine course at the time of participation. Conclusions: Inclusion of TGD people in public health surveillance and tailored public health strategies to address TGD communities' social and structural vulnerabilities may reduce barriers to COVID-19 testing.